Resolutions to Corruption Problems for Improving Thailand’s Economic Potentials - Phonvichai, Thanavath (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The aims of this study are: a) to explore both private and government sectors’ opinions and understanding about the changing situations and conditions of corruption problem and their adverse impacts on social and economic conditions in Thailand; b) to find solutions to corruption problems in order to increase the economic potentials as evidenced by other countries; and c) to propose solutions to corruption problems in order to increase Thailand’s economic potentials. The study makes use of both qualitative and quantitative research from documents and interviews. The attitudes of business people and civil servants towards corruption in Thailand show their concerns about the problem. With regard to the impact of corruption on business operations, the majority responded that their operations are rather highly affected by corruption, increasing capital expenditures by 6 to 10 percent. According to the respondents, without corruption in the country, costs would decrease by 13.9 percent. As a result, sales would increase by 10.1 percent and profits by 9.8 percent. Overall, eliminating corruption will slightly increase the nation’s competitiveness. However, the respondents finally express that although the corruption problem is resolved, Thailand’s economic growth may remain the same.